Experimental Investigation of Instantaneous Sliding Friction Coefficient of Steel Plane Worm Gear - Qiu Xinyang; Zhang Yanqin; Zhang Guanghui (Jixie chuandong)
In order to research the wear-resistant performance of steel planar worm gear,a kind of pin disc sample suitable for instantaneous line contact sliding friction is designed,the antifriction and wear-resistant performance of several typical oil is contrasted and analyzed. The correlation experimental analysis of the microscopic meshing parameter and sliding friction coefficient is carried out,the influence of load and sliding speed on the friction coefficient of transmission is quantitatively researched. The result shows that the tribology system of every point on teeth of planar worm gear pairs can be simulated successfully by line contact sliding friction test. The antifriction and wear-resistant performances of vehicle gear oil GL-5 is better,the friction coefficient decreases with the induced normal curvature radius and lubrication angle increasing. A favorable basis for the parameter selection and optimization design of steel planar worm gear is provided by the test.